Expanding frontiers in South Asian and world history : essays in honour of John F. Richards - Eaton, Richard Maxwell; Faruqui, Munis Daniyal, 1967-; Gilmartin, David, 1949-; Kumar, Sunil, 1956-2021; Richards, John F. (Cambridge University Press, 2013)
"The essays focus on 'frontiers' in multiple contexts, all relating to John F. Richards's work: frontiers and state building, frontiers and environmental change, cultural frontiers, frontiers and trade and drugs, and frontiers and world history"--Provided by publisher